2006
DOI: 10.1097/01.fpc.0000184956.16077.93
|View full text |Cite
|
Sign up to set email alerts
|

The Arg389Gly β1-adrenoceptor polymorphism does not affect cardiac effects of exercise after parasympathetic inhibition by atropine

Abstract: It appears to be unlikely that lack of Arg389Gly beta1-AR genotype-dependence of exercise-effects can be explained by influences of parasympathetic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This study, then, confirmed the hyperdynamic nature of the ␤ 1 Arg389 heart in humans. These results of exercise responsiveness have been replicated recently by another group using patients with heart failure (Sandilands et al, 2005), but the association does not appear to hold in healthy subjects (Leineweber et al, 2006). It is noteworthy, however, that direct assessment of cardiac ␤ 1 AR function by dobutamine infusion in normal subjects has shown differential responses by the ␤ 1 Arg389 genotype (Bruck et al, 2005).…”
Section: Pharmacogenetics Of Cardiac Adrenergic Signalingsupporting
confidence: 63%
“…This study, then, confirmed the hyperdynamic nature of the ␤ 1 Arg389 heart in humans. These results of exercise responsiveness have been replicated recently by another group using patients with heart failure (Sandilands et al, 2005), but the association does not appear to hold in healthy subjects (Leineweber et al, 2006). It is noteworthy, however, that direct assessment of cardiac ␤ 1 AR function by dobutamine infusion in normal subjects has shown differential responses by the ␤ 1 Arg389 genotype (Bruck et al, 2005).…”
Section: Pharmacogenetics Of Cardiac Adrenergic Signalingsupporting
confidence: 63%
“…in siblings homozygous for the Arg389 allele (6,24), HR response to acute exercise has not been associated with the Arg389Gly genotype (11,29,36,38,53). In the present study, we found a modest association between the Arg389Gly variant and baseline HR50 in blacks but not in whites.…”
Section: Discussionsupporting
confidence: 53%
“…3) (81). This holds true even when in the subjects, possible counter-regulatory parasympathetic effects were blocked by atropine: also under these conditions, exercise-induced increase in heart rate, contractility, and PRA were not different between homozygous Arg389 and Gly389 β 1 AR subjects (84). On the other hand, using a modified dobutamine stress echocardiography protocol, LaRosee et al (85) demonstrated recently that in subjects pretreated with atropine in order to exclude possible parasympathetic effects, those homozygous for the Arg389 β 1 AR variant exhibited larger inotropic and blood pressure responses than those carrying one or two Gly389 alleles.…”
Section: Functional Importance Of β 1 -Adrenoceptor Polymorphismsmentioning
confidence: 86%
“…Thus, divergent results obtained in exercise-versus dobutamine-studies could, at least partly, be due to the β 1 AR haplotype inhomogeneity of study groups. However, our recent data show that codon 49 SNP might not play a very important role: we had studied only subjects homozygous for Ser49 and had, nevertheless, found that dobutamine evoked β 1 AR-genotype-dependent effects, while exercise did not (84,86).…”
Section: Functional Importance Of β 1 -Adrenoceptor Polymorphismsmentioning
confidence: 99%